2017
DOI: 10.1002/cam4.1000
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNA‐93 regulating angiopoietin2 in the formation of malignant pleural effusion

Abstract: The biological roles of miRNAs in the development of malignant pleural effusion (MPE) are unclear. In this study, the miRNA microarray analysis was performed in two different prognosis groups of lung adenocarcinoma patients. Expression profiles of miRNAs in MPEs were identified. With the help of quantification PCR, we confirmed the expression differences of miRNAs and further analyzed their biological functions and relative target genes in vitro. The target gene of miR‐93 was estimated by online database, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Luciferase assays confirmed that miR‐106b‐5p bound directly to the 3′‐UTR of Angpt2 mRNA and inhibited its translation. Moreover, consistent with results of previous studies, knock‐down of Angpt2 in endothelial cells significantly decreased their migration and tube formation (Jiang et al, ; Liang et al, ; Qian et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Luciferase assays confirmed that miR‐106b‐5p bound directly to the 3′‐UTR of Angpt2 mRNA and inhibited its translation. Moreover, consistent with results of previous studies, knock‐down of Angpt2 in endothelial cells significantly decreased their migration and tube formation (Jiang et al, ; Liang et al, ; Qian et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Expression of Angpt2 is normally low in quiescent mature vessels, and up‐regulation of Angpt2 expression in endothelial cells leads to initiation of angiogenesis (Ahmad et al, ). Recent studies have shown that inhibition of Angpt2 signaling decreases HUVEC migration, adhesion, and tube formation (Jiang et al, ; Liang et al, ; Qian et al, ). Here, we used miRNA target prediction algorithms to identify Angpt2 as a potential target of miR‐106b‐5p.…”
Section: Discussionmentioning
confidence: 99%
“…In neuroblastoma, miR‐93 represses IL‐8‐ and VEGF‐dependent angiogenesis by targeting IL‐8 and VEGF mRNAs 127. In addition, miR‐93 reduces angiogenesis in human lymphatic endothelial cells (HLECs) by reducing angiopoietin 2 (Ang 2) expression by directly binding to the 3′UTR of the Ang 2 gene 128. Taken together, miR‐93 has dual effects on angiogenesis in different tissues and cells via multiple molecular mechanisms.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…MiR‐221 plays a major role in the regulation of the phenotypic change, differentiation and proliferation of VSMCs by inhibiting c‐kit and p27 (Kip1) mRNA expression, thereby modulating atherosclerosis remodelling 168. Moreover, miR‐221 and miR‐222 stimulates VSMC proliferation thereby accelerating neointima formation,128 which contributes to plaque progression. Reports have shown that miR‐21, miR‐146b, miR‐146a, miR‐210 and miR‐34a are up‐regulated in plaques 169.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…The role of specific miRNA, particularly miRNA-93, has been elucidated in the regulation of endothelial cell migration, proliferation, angiogenesis, and cell cycle, playing an important part in the occurrence and development of malignant pleural effusions. Its high expression is associated with a good prognosis, due to its inhibition of pleural effusion by regulating angiogenesis and lymphangiogenesis [87]. Furthermore, the differing expression levels of miRNAs, such as miRNA-182 and miRNA-210 expression, are seen in malignant pleural effusions associated with lung adenocarcinoma compared to benign pleural effusion, providing a useful role in the minimally invasive screening for diagnostic evaluations of pleural effusions [88].…”
Section: Expression Of Mirnas In Pleural Effusion Of Varying Aetiologiesmentioning
confidence: 99%